Un modelo de adopción de innovaciones: el caso del teletrabajo (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
This paper develops a model of teleworking adoption based on the principles of the technology acceptance model. The framework integrates three categories of factors influencing on teleworking adoption: technological, human resources, and organisational factors. The model fills a gap in the teleworking literature by developing research propositions that take into account different theoretical perspectives to study teleworking adoption.
Keywords: Teleworking. Information and Communication Technologies. Firm organization.